Resource potential and global warming potential of fruit and vegetable waste in China based on different treatment strategies. (1st March 2022) - Wang, Yifan; Pan, Shuping; Yin, Jun; Feng, Huajun; Wang, Meizheng; Chen, Ting
Highlights: Resource potential and global warming effect of waste management strategies studied. Multi-objective optimization model used to propose strategies for recycling FVW. Ensiling offered best resource recovery potential with 1950 MJ/t. Anaerobic digestion offered the lowest global warming potential of −31 kg CO2eq. 56% anaerobic digestion, 30% ensiling, and 14% incineration attain 60% optimal target. Abstract: Fruit and vegetable waste (FVW) contains rich resources that can be recovered by methods such as incineration, anaerobic digestion to generate heat energy, biogas, and preservation by ensiling. However, a horizontal comparison of the resource potential and environmental impact of different recycling methods employed for FVW has not been conducted. This study quantifies and computes the recycling potential and global warming potential (GWP) of anaerobic digestion, ensiling, and incineration of the FVW generated during primary production in China. First, a gray model was employed to estimate the FVW output in 2030, based on the FVW produced between 2002 and 2017. Next, the resource potential and GWP of anaerobic digestion, incineration, and ensiling were evaluated. Finally, an optimization method was utilized to analyze possible strategies of FVW recycling in 2030. Results indicate that FVW output in China is expected to increase to 170 Mt by 2030, highlighting the need for efficient treatment options. Further, the resource potential and GWP of different waste treatment strategies were notably different. The recycling potential of ensiling was the highest at 1950 MJ/t; while the GWP of anaerobic digestion was the lowest at −31 kg CO2eq. An optimization analysis suggested that the optimal target of 100% would be attained if all FVW is ensiled in 2030. The study provides a basis for informed technical decision-making related to FVW recycling options in the future.